2012
DOI: 10.1007/s10529-012-1039-8
|View full text |Cite
|
Sign up to set email alerts
|

The yeast hypoxic responses, resources for new biotechnological opportunities

Abstract: Recent advances in the knowledge of molecular mechanisms that control the adaptation to low oxygen levels in yeast and their biotechnological applications, including bioproduct synthesis, such as ethanol, glutathione or recombinant proteins, as well as pathogenic virulence, are reviewed. Possible pathways and target genes, which might be of particular interest for the improvement of biotechnological applications, are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The ability to adapt to oxygen limitation is essential for cell survival but also produces important metabolic, functional and structural changes in the cell [19]. Cells can adapt to growth under oxygen limitation, termed hypoxia or microaerobic conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to adapt to oxygen limitation is essential for cell survival but also produces important metabolic, functional and structural changes in the cell [19]. Cells can adapt to growth under oxygen limitation, termed hypoxia or microaerobic conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms of oxygen sensing and responses to hypoxia in yeast and pathogenic fungi have been reviewed recently [1][4]. C. neoformans utilizes Sre1, the mammalian sterol regulatory element-binding protein (SREBP) homolog, to control sterol homeostasis, oxygen sensing, and virulence in mice [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no obvious SREBP orthologs in Saccharomyces cerevisiae or in any of the species belonging to the Candida clade. These yeast cells respond to limited-oxygen conditions by inducing expression of a large number of hypoxic genes, which encode oxygen-related functions in respiration and biosynthesis of heme, lipids, cell-wall and membranes [2], [4]. Studies using the hypoxia mimetic compound CoCl 2 revealed that the ability of C. neoformans to grow in low oxygen conditions was linked to mitochondrial function, the ability of cells to respond to reactive oxygen species, and gene expression associated with ubiquitination as well as sterol and iron homeostasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…pressed gene expression under high concentrations of fermentable sugars (Gascón and Lampen 1968) and in the absence of molecular oxygen (Plattner et al 1970). Since S. cerevisiae is Crabtree-effect positive, it produces ethanol even in the presence of oxygen and glucose rather than the tricarboxylic acid (TCA) cyclerelated constituents (González Siso et al 2012).…”
Section: Sake Brewing Processmentioning
confidence: 99%